2003
DOI: 10.1016/s1534-5807(02)00401-x
|View full text |Cite
|
Sign up to set email alerts
|

The Forkhead Transcription Factor Foxo1 Regulates Adipocyte Differentiation

Abstract: An outstanding question in adipocyte biology is how hormonal cues are relayed to the nucleus to activate the transcriptional program that promotes adipogenesis. The forkhead transcription factor Foxo1 is regulated by insulin via Akt-dependent phosphorylation and nuclear exclusion. We show that Foxo1 is induced in the early stages of adipocyte differentiation but that its activation is delayed until the end of the clonal expansion phase. Constitutively active Foxo1 prevents the differentiation of preadipocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
590
3
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 667 publications
(651 citation statements)
references
References 32 publications
46
590
3
5
Order By: Relevance
“…In particular, Foxo1 has an essential role in maintaining glucose homeostasis during fasting. In addition to the aforementioned function as a master regulator of gluconeogenesis in the liver, its inhibitory effects on adipocyte differentiation [5] and pancreatic b-cell function [4] (Figure 2) also support the notion that Foxo1 belongs to a group of genes evolved for adaptation to starvation. It also represents a typical causal factor for the development of obesity and type 2 diabetes, evidenced by numerous studies showing that Foxo1 halploinsufficiency prevents insulin resistance and diabetes in several mouse models, including Insr C/K [21], Irs2 K/K [4] and high-fatdiet-fed mice [5].…”
Section: Updatesupporting
confidence: 55%
See 1 more Smart Citation
“…In particular, Foxo1 has an essential role in maintaining glucose homeostasis during fasting. In addition to the aforementioned function as a master regulator of gluconeogenesis in the liver, its inhibitory effects on adipocyte differentiation [5] and pancreatic b-cell function [4] (Figure 2) also support the notion that Foxo1 belongs to a group of genes evolved for adaptation to starvation. It also represents a typical causal factor for the development of obesity and type 2 diabetes, evidenced by numerous studies showing that Foxo1 halploinsufficiency prevents insulin resistance and diabetes in several mouse models, including Insr C/K [21], Irs2 K/K [4] and high-fatdiet-fed mice [5].…”
Section: Updatesupporting
confidence: 55%
“…Similar to Foxa2, Foxo1 is an effector of insulin signaling in hepatocytes [3], pancreatic islets [4] and adipocytes [5]. Foxo1 promotes gluconeogenesis in the liver during fasting and is inactivated upon feeding through insulin-signaling-mediated phosphorylation and nuclear exclusion [3].…”
Section: Foxa2 Inactivation Causes Liver Steatosis and Insulin Resistmentioning
confidence: 99%
“…In rodent beta cells, FOXO1 controls various cellular responses including proliferation [4,[26][27][28][29]. Our ex vivo analyses demonstrated a progressive decrease in the localisation of nFOXO1 within proliferating cells, suggesting that FOXO1 may be involved in regulating cell cycle progression in the human fetal pancreas after 12 weeks of a c fetal age.…”
Section: Discussionmentioning
confidence: 64%
“…The majority of studies have demonstrated that FOXO1 inhibits cell proliferation at multiple phases of the cell cycle in various cells and tissues [3,[25][26][27][28][29]. To determine if there is a role for FOXO1 in cell proliferation during human fetal pancreas development, co-localisation of nFOXO1 with Ki67 was assessed (Fig.…”
Section: Presence Of Nfoxo1 In Proliferating (Ki67 + ) Cells During Hmentioning
confidence: 99%
“…Dr Domenico Accili elegantly proposed that the FOXO family of transcription factors controls metabolism in several tissues, 4 including the pancreas and the liver, where Foxo1 regulates gluconeogenesis with the help of PGC-1 (addressed earlier in the day by Pere Puigserver). Foxo1 also impacts on adipogenesis in mice 5 and flies, 6 likely during the first phase of clonal expansion during the differentiation process. Foxo1 acts downstream of the insulin signaling cascade, so it is not surprising that in mice, deletions of Foxo1 or the insulin receptor affect metabolism in a convergent molecular pathway and with convergent consequences on insulin sensitivity and adipose tissue development.…”
mentioning
confidence: 99%